PRINCIPLES OF CREATING THE CREATIVE STYLE IN TRANSLATION - Nozima Kholikova (American Journals, 2022)
The purpose of the translation is to reflect the content of the original, to gain a deep understanding of the artist's style. In this case, the translator needs not only to know the meaning of the word, but also to understand the aspects of meaning in the text. The only way to determine the figurative and contextual meanings of artistic words in the work is related to knowing the author's original style.
Keywords: Style, author, translation, studies, scientific, translator, content, context, meaning.